An anomalous engenderment of a common scenario: upper gastrointestinal bleeding - Vasa, Tirth Nayan; Prabhu, Mukhayprana; K. V., Rajagopal; Sahu, Devavrata; Bhatia, Harnish (International Journal of Research in Medical Sciences, 2017)
Upper gastrointestinal bleeding (UGIB) includes hemorrhage originating from the esophagus to the ligament of Treitz. It is a gastrointestinal emergency that can result in significant morbidity, mortality, along with laborious utilization of health-care resources. With the advent of definite management protocols, the recent trends have revealed that patients rarely die from exsanguination, with decompensation of the underlying disorders, rather, proving to be causative of the same. Rapid assessment, resuscitation, and early endoscopic investigation serve as the foundation of early management. Common sinister underlying aetiology include Oesophageal Varices, Peptic Ulcer Disease, NSAID Induced Acute Gastritis or Malignancy. Arising from a conglomeration of aetiologies, an infrequent one, is a silently sinister pseudoaneurym rupturing into the stomach, stemming from a visceral artery. Since the first description by Beaussier in 1770, the condition has been detected with increasing frequency, primarily as a consequence of the increasing use of accurate imaging methods. Coeliac artery aneurysms (CAAs) occur in approximately 0.2% of the overall population and constitute approximately 4% of all visceral artery aneurysms (VAAs). Their risk of rupture is estimated at 10% to 15% and is associated with high mortality. Associated risk factors include atherosclerosis, hypertension, systemic inflammation, trauma, collagen vascular disease, infection, fibromuscular dysplasia, and cirrhosis